TEKNIK PENGENDALIAN ALIRAN PERMUKAAN YANG EFEKTIF PADA USAHATANI LABAN KERING BERLERENG - A Noeralam; Sitanala Arsyad; Iswandi Anas (Jurnal Ilmu Tanah dan Lingkungan, 2003)
The aims of this study were to find out the effects of runoff control techniques and cropping patterns on the runoff rate of sloping upland farming. A series of factorial experiments were conducted on a Lithic Dystrudepts located at three different sloping uplands in Malang, East Java. The area belongs to the C type of Oldeman climatic zone. The three runoff control techniques were soil pit with vertical mulch (T1), soil pit with ridge and vertical mulch (T2), and soil pit with a ridge (T3). The two sequential cropping patterns were maize (Zea mays L.) - soybean (Glycine max (L.) Merr.) - maize (P1), and peanut (Arachis hypogaea) - maize - soybean (P2). The result indicates that runoff control techniques decrease rate of runoff by 88%, for soil pit with ridge technique, 86% for soil pit with ridge and vertical mulch technique, and 84% for soil pit with vertical mulch technique. The relationship ofrainfallJx) with run off(y) can be expressed by y = 0.05x; r = 0.92 in cropped plot andy = 0.30x; r = 0.90 in bare plot. Keywords: ridge, soil pit, vertical mulch